ANALISIS KEBERLANJUTAN USAHATANI TOMAT DI DESA SIDAMANGURA KECAMATAN KUSAMBI KABUPATEN MUNA BARAT - Asma, Asma; Nalefo, La; Arif, La Ode Kasno (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The objective of this study is to ascertain the sustainability of tomato farming in Sidamangura Village, Kusambi District, West Muna Regency. The present study was based on the information provided by 58 tomato farmers residing in Sidamangura Village. The informants were selected deliberately, resulting in a total of six informants. The data were collected using a combination of methods, including observation, documentation, and in-depth interviews with interview guides. The focal point of this study was the sustainability of tomato farming. The subsequent analysis of the data was conducted using qualitative analysis methods. The findings indicated that tomato farming in Sidamangura Village possesses the capacity to persist, despite the presence of variations across various dimensions. In the ecological dimension, sustainability is indicated by the low potential for pests and diseases and the use of fertilizers. However, the use of pesticides is a hindering factor. In the economic dimension, sustainability is supported by income and market access, while production factors continue to encounter challenges. Concurrently, within the social dimension, sustainability is bolstered by factors such as the level of education, the productive age of farmers, and the involvement of families. The sustainability of farming is influenced by ecological and economic factors, as well as the social role of farming families. The sustainability of tomato farming in rural areas is contingent upon a number of social factors, with particular emphasis on the role of family participation.